CODESRIA Bulletin Online, No. 25, November 2021 - African Solutions to African Problems: Appropriation in World Politics - Aubry, Ayrton (CODESRIA Bulletin, 2021)
Security co-operation in Africa has been studied through multiple approaches in International Relations, from institutionalism to constructivism and regionalism. African Union policies and norms, such as the recent African Peace and Security Architecture, or the norm of ‘bringing African Solutions to African Problems’, have been thoroughly examined by many authors, especially in the domain of security. Although most of these discussions bring stimulating elements to the study of Africa in International Relations, we argue that they fail to grasp fully what ‘appropriation’, or ‘Africanisation’, means. Our research digs deeper into this question, delving into what African political theory says about it, particularly looking at the works of Frantz Fanon, Ngugi Wa Thiong’o and Paulin Hountondji. Introduction he ability of African states to bring their own solutions to national or continental security problems has been a topic of conversation since the 1960s wave of independence, and even before.1 This question goes beyond solving actual issues within the continent; it also raises the urgent necessity of African states finding solutions before exogenous intervening actors get in the way2—in other words, for African actors to ‘Africanise’ their security. Although the first part of the question is systematically studied in the literature on security cooperation, surprisingly, the latter tends to be overlooked. While some works call for a greater inclusion of African studies in International Relations (Abrahamsen 2017), the implications of such an approach usually do not go beyond an introductory level, and still regularly assume African perspectives or take them for granted. Academic interest in security cooperation in Africa is not new, and different literatures on the subject can be distinguished, all at the intersection of numerous and thriving discussions in International Relations in general. For instance, regionalism is a major paradigm in the field, largely influenced by studies of European integration. In addition, the study of the ‘African Solutions’ norm is regularly conducted through liberal and constructivist perspectives, two mainstream theories of International Relations. Other approaches range from a Gramscian stable hegemony (Dauda, Ahmad and Keling 2018) to a realist hegemony analysis (Moller 2009). Institutionalist perspectives insist on institutional initiatives put forward by the AU and African states in handling security issues. Many of these works focus on the African Peace and Security Architecture (APSA) and its different components, as well as on co-operation and competition between the AU, other African regional organisations and the United Nations (UN) (Suzuki 2020; Dersso 2012; Coleman 2011). While they provide a precise understanding of power dynamics in conflict resolutions, we argue that these approaches give only surface reflections of the meanings of ‘Africanisation’. Worse still are studies that consider AU mechanisms as a simple reproduction of other international institutions, such as the EU (Schmidt 2010). In these cases, little agency is given to African institutions in the imagining and implementation of new policies, and the emphasis is rather on co-operation and knowledge transfer from one side of the Mediterranean Sea to the other. The regionalist view sees the process of ‘African Solutions to African Problems’ as a norm produced by African states, and/or as a point of entry into the international system (Coleman and Tieku 2018; Duursma 2020). This constructivist-inspired approach is the most promising, since it seems to carry the most likely framework for identifying the dynamics of appropriation in the policies of the AU. To enter this subject by the norm door is a great opportunity to grasp the appropriating moves of African institutions, because it is accompanied by theoretical reflections about them. Works that build on norms draw on theories in the constructivist literature in International Relations, such as norm cycles or security communities. Our point in this article is to renew our understanding of the ‘African Solutions to African Problems’ norm and to enrich the discussion about Africa in International Relations. We do so by assessing the existing literature on the topic and by looking at more precise definitions of appropriation that position it as the factor to be explained rather than the explaining factor in the study of AU security policies. Among others, Frantz Fanon, Ngugi Wa Thiong’o and Paulin Hountondji reflected one way or another on Africanisation. All of them seem to be potential pathbreaking sources in the literature about the Africanisation of security and about recentring Africa in the discipline of International Relations in general, even though—quite surprisingly— their works are rarely mentioned in that literature. In this paper, we aim to contribute to the decentring of International Relations literature, by identifying the meanings of the term ‘Africanisation’ and discussing the limits of the IR literature that has tackled this concept until now. We begin with a critical assessment of existing approaches to ‘African Solutions to African Problems’ in the IR literature, before presenting an overview of ‘Africanisation’ by the three aforementioned authors. Their arguments underline, in particular, the need to depart from the still widely shared assumption of a unanimity, and insist on much more historicisation of the topic. Appropriation or Transfer? A Critical Assessment of Africanisation in the IR Literature The constructivist approach predominates in studies of the African Solutions norm. Some of them frame the AU as an autonomous security community, and build on successive studies in IR by Karl Deutsch and then Adler and Barnett (Adler and Barnett 1998). Benedikt Franke brings into the discussion a very interesting take on the evolution of norms of security co-operation in African regional institutions (Franke 2008). The constructivist literature mobilises concepts such as ‘security regime’ to describe the norm of Africanisation (Vlavonou 2019). From this perspective, African Solutions to African Problems can also be portrayed as a ‘shared Responsibility to Protect’ (Besada, Goetz and Werner 2010), as part of a broader reflection on the AU, in its shift from a principle of non-interferenceto a principle of non-indifference. When the AU is studied as a community of practice, the hostility to international intervention that prevails in Africa is highlighted, as chapter 4 of the AU Charter illustrates, in its ‘promotion of self-reliance’ (Glas 2018). The role of African actors in the different steps of the norm cycle has been thoroughly studied by several scholars in the last decades, fully placing Africa at the centre of international theory. Building on Keck, Sikkink and Finnemore’s works, studies have examined how African actors shape the process of creation of global norms, how norms diffuse on the continent, how their implementation leads to adaptation (which comes close to some understanding of appropriation), and how global norms are contested in Africa (Coleman and Tieku 2018). Studies in norm localisation, for instance, contribute a lot to our understanding of African actors as very much engaged, and not just shaped by global dynamics or at the mercy of ruthless and corrupt leaders. Norm localisation forces us to consider local contexts in depth in deploying this conceptual tool. Such works rely on meaning-in-practice methods and help us to understand the shift from the Organisation of African Unity’s non-intervention norm to the AU’s non-interference norm (Williams 2007). For Coleman and Tieku, norms can be not only localised but also radically renegotiated and deprived of their original meaning (Coleman and Tieku 2018). Norm circulation is thus not only about the expansion of practices from an original centre (Bull and Watson 1984); it also goes through a process of successive captures and reformulations. The literature on African agency has also brought substantive elements to the discussion on Africanisation, by looking at the room African actors have in which to manoeuvre, and by insisting on interactions rather than relations of one-way domination (Brown and Harman 2013). The African Solutions norm is presented in such a context, and powerfully highlights how states in European history have been studied as a construct of agency, while states in Africa have been studied as a construct of institutionalised dependence (Williams 2013). The African Solutions norm allows us to move away from the narrative about constructed dependence in Africa and to focus on actual initiatives by African actors as well as the broader context in which these take place. Other works in this vein invite us to look at historical manifestations of the African Solutions norm, and to acknowledge how entangled it has been with the anticolonial struggle for a long time (Franke 2009). These approaches are crucial in moving the discussion forward and away from the theories of quasistates and negative sovereignty that have dominated the field from the 1960s (Roth 1968; Jackson 1990; Jackson and Rosberg 1982), which evolved into the theories of extraversion and state survival in the 1990s (Clapham 1996). Those theories still influence some of the literature, whereas others have considered the question of Africa’s place in International Relations following IR mainstream theories to a greater or lesser extent (Dunn and Shaw 2013). However, these works almost systematically approach Africanisation as an explaining factor, claiming to situate it in a large set of policies by the AU (Duursma 2020): in these works, Africanisation is a raw list of policies and institutions created by the AU. We argue that, by doing so, they end up overlooking Africanisation as the factor to be explained and directly take it for granted, or avoid the question by presenting it as a reaction to the withdrawal of intervening powers from the continent in the 1990s, letting the 1994 genocide against the Tutsi in Rwanda happen, for example. Subsequently, these approaches tend to use theoretical shortcuts, failing to bring insights from African studies into the analysis. By focusing on African Solutions to African Problems as a simple transfer of knowledge and not an appropriation, they miss a large part of the picture. Most of the aforementioned works pay little attention to how the principles of the Africanisation norm were discussed within the AU or in other places by other African actors.3 Seriously considering the concept of appropriation in analysing the Africanisation of security is a way for us to go beyond the weaknesses of the liberal and the constructivist theoretical perspectives identified above. First of all, it highlights the limits of viewing AU policies as a simple copy of European integration, which the institutionalist literature does. Constructivist studies in terms of knowledge transfer, or which measure the weight of African militaries in peacekeeping operations, are useful for the information they provide, but their theoretical outcome is weak. Furthermore, the emphasis on appropriation would contribute to renewing the constructivist literature. We consider in this article that a focus on appropriation takes us a step further in the direction of postcolonial reflections on recentring Africa in International Relations, by bringing a substantive epistemological perspective to the discussion while associating it with empirical observations (Iñiguez De Heredia and Wai 2018). Postcolonial writings regularly remark on the systematic depiction of African states and African actors as ‘lacking’ something, and the deduction that the adoption of Western tools of governance could ‘save’ the continent from its security issues (Iñiguez De Heredia and Wai 2018). Historicism in the study of African issues in International Relations has been highlighted over the last two decades, in the work of John Hobson (2012) and Robert Vitalis’ White World Order, Black Power Politics (Vitalis 2017). Both argue that the questions of race and empire are constitutive of the discipline of International Relations, as they were the main preoccupation of the founders of the discipline. This vocabulary was erased after World War II, but because no epistemological review was undertaken, the changes in the discipline in this regard were marginal. Postcolonial studies have been calling for an epistemological reflection in IR for the last decades. Their major theoretical breakthrough was in identifying the ‘first the West, then the rest’ narrative about African actors (as well as other postcolonial actors) in the international system (Iñiguez De Heredia and Wai 2018). The postcolonial perspective exposes this narrative as not just a weakness or a blind spot of the literature, but a constitutive part of the discipline of International Relations. This means that it is not enough to just ‘bring Africa back in IR’ without epistemological changes (NdlovuGatsheni 2018). The Meanings of Africanisation Africanisation is a widely used term in the study of African issues, and covers an incredibly large range of topics, from religion (as in, ‘the Africanisation of Islam’) to administration (‘the Africanisation of civil servants in the 1950s and 1960s’), philosophy and development. It is all the more striking that no work, so far, has studied the relationship (or the absence of relationship) between those different kinds of Africanisation, as there is no clear definition of what ‘appropriation’ and ‘Africanisation’ mean. In this part, we present an overview of some uses of the concepts of Africanisation and appropriation and explore how these approaches can help us advance the discussion of appropriation in the IR literature. We present the Fanonian perspective on Africanisation, Ngugi Wa Thiong’o’s ‘re-membering Africa’, and then turn to Hountondji’s take on the concept. Fanon Fanon develops a large part of his analysis around the concepts of Africanisation and appropriation, especially in The Wretched of the Earth, A Dying Colonialism and Toward the African Revolution. In his study of Fanon, Ato Sekyi-Otu defines appropriation as ‘the activity of coming into one’s own when there is no primal self to return to, no inviolate native essence to recapture’ (Sekyi-Otu 1996: 184). This implies a different take on the issue of modernity in a colonial and postcolonial context. Indeed, appropriation in that sense does not mean to erase the experience of colonisation to return to what is imagined as having existed before. In the Fanonian sense, appropriation happens through the liberation struggle that produces and brings to the forefront a new generation of cadres. Fanon brings the concept of Africanisation to the heart of the African liberation struggle, assuming that the liberation struggle emanates from an endogenous process and that liberation movements should be analysed as such (Neocosmos 2016; Biko 1998). This means applying, for instance, what Gibson calls ‘new subjectivities’, moving from regarding Africans as the ‘wretched of the earth’, as a substance or a mass, to studying them as subject and as reasoning protagonists (Gibson 2011). Steve Biko has a very similar view, insisting on appropriation as key to the struggle, to avoid the reproduction of domination (Biko 1998). Thus, when associated with liberation, appropriation means that it must be taken, and not given, hence Fanon’s emphasis on violence in the first chapter of The Wretched of the Earth. Ato Sekyi-Otu calls this a ‘dialectic of experience’. The best illustration of appropriation can be found in Fanon’s example of the bridge, in the chapter ‘The Pitfalls of National Consciousness’: The bridge should not be ‘parachuted down’ from above; it should not be imposed by a deus ex machina upon the social scene; on the contrary it should come from the muscles and the brains of the citizens. Certainly, there may well be need of engineers and architects, sometimes completely foreign engineers and architects; but the local party leaders should be always present, so that the new techniques can make their way into the cerebral desert of the citizen, so that the bridge in whole and in part can be taken up and conceived, and the responsibility for it assumed by the citizen. In this way, and in this way only, everything is possible (Fanon 2004: 201). This example illustrates Ato SekyiOtu’s distinction between a ‘lived experience’, which allows appropriation to happen, and an ‘immediate knowledge’, which would be the result of a failed appropriation. Ngugi Wa Thiong’o In Something Torn and New, Ngugi Wa Thiong’o reflects on the effect of colonisation on African languages, and how they were dismissed (Thiongʼo 2009a). He argues that colonisation was about two joint processes of dismemberment and fragmentation of the continent. Although he does not frame the continent’s repair in terms of Africanisation or appropriation, Wa Thiong’o considers that the answer is to ‘re-member’ Africa. Ngugi Wa Thiong’o plays here on two senses of the word: the first being about remembrance, and the second about reformation. Colonisation and European expansions were indeed about imposing, or rather submitting the world to, European memories—for instance, by naming places based on the European experience (New Hispaniola, New York, etc.). This replacement of an imaginary by another had a linguistic dimension that, for Ngugi Wa Thiong’o, took the form of linguicide in the Americas and the starvation of African languages on the continent. Devaluing language was a key weapon in colonisation, but the politics of decolonisation have not paid enough attention to language in the healing process (Thiong’o 2018). Africanisation, or appropriation, presupposes a deep effort of conceptualisation in African languages, or at least thinking about the consequence of colonisation on African languages and how to move beyond them. Re-membering, in the case of Ngugi Wa Thiong’o, is associated with a quest for ‘wholeness’, ‘that has underlain African struggles since the Atlantic slave trade’ (Thiongʼo, 2009b: 25). In our opinion, this wholeness has an important place in the contemporary rhetoric of Africanisation, which does not appear in analyses that focus solely on Africanisation as a process of transfer rather than as a process of appropriation. Ngugi Wa Thiong’o’s approach brings us to another understanding of Africanisation, not directly in terms of appropriation, but in terms of changing the scale of thought. Africanisation indeed carries with it the idea of a continentalisation of thoughts, or the consideration of issues through the collective lens of Africans in the continent and the diaspora. And this follows Wa Thiong’o’s use of the term ‘wholeness’, which is the object of the quest by African actors. As a matter of fact, he mentions the creation of the ANC in 1912 as the birth of African Renaissance because it brought different African cultures together ‘to fight for the same place under the sun’ (Thiong’o 2009b). Hountondji In African Philosophy: Myths and Reality, Paulin Hountondji (1996) opens wide a whole new set of discussions on African philosophy by rejecting practices of ethnophilosophy. We argue that Hountondji, by warning us against the ‘illusion of unanimity’, invites us to shed light on varieties of definitions of Africanisation. Furthermore, his work on the concept of ‘appropriation’ and his reflections on indigenous knowledges invite us to look beyond what is often described as a mere ‘transfer’ of knowledge in the IR literature. Hountondji draws on Samir Amin’s concept of economic extraversion to reflect upon what he identifies as an intellectual extraversion in African universities. He views this extraversion as two-sided: one refers to African works that answer to a European-invented philosophical discussion about Africa; the second highlights that knowledge is extracted from the continent and published in Western universities. To Hountondji, the question of the international structure of scientific production implies to think about an ‘African appropriation of knowledge’ (Hountondji 2002). Part of these reflections are pursued in Hountondji’s edited volume, Endogenous Knowledge, where he notes a dependency in African scientific production, in which scientific orientations are the result of Western needs (Hountondji 1997). This situation is the result of a transfer rather than an appropriation of scientific policies in African contexts. Besides his work on indigenous knowledge, Hountondji gives us methodological insights with his reflections on ethnophilosophy. Starting from a critique of Placide Tempels’ Bantu Philosophy (1959), he recalls that although Placide Tempels acknowledged the humanity of Bantu people, he was looking for a ‘supplément d’âme’ for Europe as much as he was making sure that the colonial project would go on. By overlooking this context, works in African philosophy end up reproducing European discussions. Appropriation here is in the autonomous practice of philosophy, understood as answering African problems and sparking discourses rather than imaginaries about immoveable and unanimous belief systems, collective systems of thought that make any philosophical activity impossible. Ethnophilosophy can in that sense be considered a failed appropriation of philosophy. While they write in different contexts, Fanon and Hountondji both consider the outcomes of a failure of appropriation. To Fanon, in a context of liberation struggle it would result in a weak conceptualisation of liberation ideology and the confiscation of the liberation by neoliberal projects. The liberation struggle’s transformative effect can avoid failed appropriation. Hountondji’s view of the outcome of a failed appropriation is rather formulated in terms of extraversion, following Samir Amin’s analysis of African economies. This last consideration is a pivotal point in the discussion around decentring IR that we propose in the next part. Most works in political science interested in the African Solutions norm still assume that African states systematically mobilise strategies of extraversion. We argue that these assumptions see only the last stage of a failed process of appropriation, whereas the picture is much broader in reality and the possibilities are not so narrow. All in all, these theoretical discussions about the definitions of appropriation highlight how it is more about the process than about the outcome or its cultural justification. Conclusion: Towards a New Approach of Appropriation in World Politics What can Fanon, Wa Thiong’o and Hountondji bring to our understanding of the Africanisation of security? To begin with, they urge us to add a dialectical aspect to our methods. For a long time, Africanisation has been the explaining factor in the political science literature, while considering the dialectic of Africanisation would make us study Africanisation for itself, as the factor to be explained. So far, we have explored how the different literatures in IR tackle the issue of Africanisation, and identified several ways to take the discussion further. These steps are necessary for whoever wants to build on the existing literature, and this is all the more important with postcolonial theories that are often criticised as repeating the same observations (Alejandro 2019). Now is the time to integrate those critiques and the authors we present above into some of the constructivist approaches that we dealt with in the first part of this paper, and to formulate a proposition to renew our approaches of appropriation in general and Africanisation in particular. When it comes to the Africanisation of security, what lessons can be learned from the different works that we review in this paper? At the empirical level, the role of elites formation is crucial in this process. Besides, the heterogeneity of situations leads us to think that Africanisation is also an everchanging process, and its study should not be limited to a set of policies. This should invite scholars to pay attention to where African military officers are educated, for instance. Fanon mobilising the concept of Africanisation in a context of liberation struggle does not mean that we need to create a framework of liberation struggle in our understanding of the AU’s contemporary security policies. It means, however, that the genealogy of Africanisation needs to be traced, to have a better understanding of how different or similar the security policies of the AU are from projects that were elaborated during the liberation struggle. In that sense, Gibson’s remarks on ‘new subjectivities in the usages of Fanon in South Africa are very helpful and urge us to pay attention to what the Africanisation of security means in everyday life and in the political scene. For instance, how is the African Solutions norm debated in Ghana? Such a framework would imply giving weight to how ‘appropriation’, or ‘security’ is expressed in Wolof, Akan or other African languages. It would also fit with Hountondji’s claim that unanimity is an illusion and provide us with a pluralistic view of Africanisation. It would allow us to distance ourselves from the narrative of patronage politics and politics of state survival, by looking at sometimes contradicting interests, and more specifically how these interests are formed. While some definitions of Africanisation of security have been attempted, only a few consider the concept of appropriation seriously and we argue that this explains why current discussions about the norm of African Solutions to African Problems bring so little to the discussion about Africa in the discipline of International Relations. Although analyses around the African Solutions norm bring useful information, they undermine its theoretical potentialities. These analyses, although they question the long-standing assumptions of passiveness and lack of African actors in the international system, sometimes fail to interrogate the ontology of Africa’s international relations, and end up focusing only on ‘Westernised’ behaviours of African states (reproducing the latent Eurocentrism of ‘first the West then the Rest’ reasoning). Our approach, to use Siba Grovogui’s words, ‘refutes the established theories of postcolonial independence that equate the transfer of political power, however limited, from the coloniser to the colonised with African self-determination and an assumption of national sovereignty’ (Grovogui 1996). We have presented several ways to go beyond the understanding of appropriation as a mere transfer. Appropriation, and Africanisation in particular, implies much more than that. We have tried in this paper to pay more attention to the meanings of Africanisation, considering it as the factor to be explained rather than taking it for granted. The works of Fanon, Wa Thiong’o and Hountondji provide us with opportunities to articulate our approaches to the meanings differently. Notes Kwame Nkrumah began his 1957 speech at the dawn of Ghanaian independence saying that Africa was ‘ready to fight its own battles and show that after all the black man is capable of managing his own affairs’, as quoted in Getachew 2019: 1.{\\i{}Worldmaking after empire: the rise and fall of self-determination} (Princeton, New Jersey: Princeton University Press, 2019). For instance, before French intervention in Mali in 2013, discussions were held between the African Union and ECOWAS to intervene in Mali as well. This didn’t prevent the deployment of the Serval operation, and the African force was later integrated into a larger UN Peacekeeping With the exception of Tieku 2017. it consists of fifty-four members, a ten-member Commission, political organs, such as the Assembly, PanAfrican Parliament, and a body where civil society groups are The AU seeks the political and socio-economic integration of the African continent and has emerged as a key player in international politics. Since its creation, the AU has tackled a wide range of issues, including health epidemics (Ebola).